An Alternative Perspective towards Reducing the Risk of Engineered Nanomaterials to Human Health. Issue 36 (5th August 2020) - Clift, Martin J. D.; Jenkins, Gareth J. S.; Doak, Shareen H.
Abstract: To elucidate the impact of human exposure to engineered nanomaterials, advanced in vitro models are a valid non‐animal alternative. Despite significant gains over the last decade, implementation of these approaches remains limited. This work discusses the current state‐of‐the‐art and how future developments can lead to advanced in vitro models better supporting nano‐hazard assessment. Abstract : This article intends to summarize the current climate of in vitro systems for (nano)particle toxicology. It considers the plethora of different models and approaches being both employed and developed within the field. This work provides a succinct update regarding the advances within the field of alternative technologies.